Leukotrienes in cerulein-induced acute pancreatitis in rats and effect of octreotide - , Galip ERSÖZ, Afik HÜSEYİNOV and , Ömer ÖZÜTEMİZ and , Gül YÜCE and , Işıl ÇOKER and , Yücel BATUR (Turkish Journal of Gastroenterology 1, 2019)
-